Effect of exercise training before and after bariatric surgery: A systematic review and meta‐analysis. (3rd June 2021) - Bellicha, Alice; van Baak, Marleen A.; Battista, Francesca; Beaulieu, Kristine; Blundell, John E.; Busetto, Luca; Carraça, Eliana V.; Dicker, Dror; Encantado, Jorge; Ermolao, Andrea; Farpour‐Lambert, Nathalie; Pramono, Adriyan; et al.
Summary: We aimed to assess the effectiveness of exercise training programs in adults with severe obesity undergoing bariatric surgery. A systematic search of controlled trials published up to October 2019 that assigned participants to either a preoperative or postoperative exercise training group or a nonexercise group was performed. Meta‐analyses were conducted using random‐effects models. Twenty‐two training programs were assessed (18 performed after bariatric surgery). The effect of preoperative exercise training on postsurgery outcomes was reported in only one study. Compared with the control condition without exercise, postoperative exercise training led to higher weight loss ( N  = 14, mean difference [95% CI] = −1.8 [−3.2; −0.4] kg, P  = 0.01), fat loss ( N  = 9, P  = 0.01), increase in VO2 max ( N  = 8, P  < 0.0001), and increase in muscle strength ( N  = 9, P  < 0.0001). No significant effect was found on lean body mass ( N  = 11). Preliminary evidence suggests a beneficial effect of postoperative exercise training on bone mineral density ( N  = 3, P  < 0.001) and weight maintenance after the end of the intervention ( N  = 2, P  < 0.001) but no significant effect on quality of life ( N  = 2), habitual physical activity ( N  = 2), or cardiometabolic outcomes ( N  < 4). In conclusion, exercise training performed after bariatric surgery improves physical fitness and leads to a small additional weight and fat loss and may prevent bone loss and weight regain after bariatric surgery.